2010
DOI: 10.3109/09537100903470306
|View full text |Cite
|
Sign up to set email alerts
|

The platelet functions in patients with ankylosing spondylitis: Anti-TNF-αtherapy decreases the mean platelet volume and platelet mass

Abstract: The present study was designed to investigate the interaction between platelet indices (mean platelet volume (MPV), platelet count (PLC) and platelet mass (PLM)), inflammatory markers and disease activity in ankylosing spondylitis (AS) subjects. The effects of anti-TNF-alpha therapy and conventional treatment on platelet indices were also compared. We studied 68 patients with AS (group I, 46 men, age: 36.4 +/- 6.9 years) and as control group 34 age and sex-matched healty subjects. All patients received convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 15 publications
4
75
0
1
Order By: Relevance
“…In the same way, we investigated if there were relationships between PLR and MPV values and disease activity in AS or not. Inconsistently with previous studies about several chronic inflammatory diseases including chronic obstructive pulmonary disease, 15 inflammatory bowel disease, 18 RA and AS, [19][20][21] we found that MPV did not reflect disease activity in AS since its levels were similar in healthy controls as well as patients with mild and moderate to severe disease activity. Similar to the present results, no significantly different levels of MPV were reported in patients of hemodialysis, renal transplanted, peritoneal dialysis and chronic renal failure patients when compared to each other 34 as well as in patients with advanced stage endometriosis.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In the same way, we investigated if there were relationships between PLR and MPV values and disease activity in AS or not. Inconsistently with previous studies about several chronic inflammatory diseases including chronic obstructive pulmonary disease, 15 inflammatory bowel disease, 18 RA and AS, [19][20][21] we found that MPV did not reflect disease activity in AS since its levels were similar in healthy controls as well as patients with mild and moderate to severe disease activity. Similar to the present results, no significantly different levels of MPV were reported in patients of hemodialysis, renal transplanted, peritoneal dialysis and chronic renal failure patients when compared to each other 34 as well as in patients with advanced stage endometriosis.…”
Section: Discussionsupporting
confidence: 69%
“…33 Moreover, significantly decreased levels of MPV were reported after anti-TNF-a therapy in patients with AS. 20 Recently, MPV that was investigated in inflammatory bowel disease, 18 chronic obstructive pulmonary disease, 15 RA and AS [19][20][21] and PLR which was evaluated in some cancers like gastric, 14 colon, 22 and non-small cell lung cancers 23 have become to be prominent markers to indicate inflammatory status and prognosis of several diseases, but there is no cut-off level reported before for PLR and MPV as well as NLR. In the same way, we investigated if there were relationships between PLR and MPV values and disease activity in AS or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Similarly, MPV values decreased after treatment of active disease in patients with ankylosing spondylitis. 25 Furthermore, higher MPV values were shown in patients with severe obstructive sleep apnea leading to cardiovas� cular complications compared to a control group in a study with 95 subjects. 26 A significant decrease was found in MPV after continuous positive airway pressure (CPAP) treatment for 6 months in a similar group of patients.…”
Section: Coban Et Almentioning
confidence: 99%
“…[11][12][13] MPV has been evaluated in chronic inflammatory diseases such as rheumatoid arthritis, ankylosing spondylitis, and Behçet's disease. [14][15][16] Due to their inflammatory roles, MPV and NLR may be used as inflammatory markers in LN, which is known as a systemic, autoimmune complication of SLE. Yavuz and Ece 17 have suggested MPV as a disease activation indicator for juvenile SLE nephritis patients.…”
mentioning
confidence: 99%